2017
DOI: 10.26451/abc.04.04.06.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Cows

Abstract: -Domestic cows (Bos taurus) are consumed worldwide as beef and veal, kept as dairy product producers, employed as draft animals in labor, and are used for a long list of other products, including leather and manure. But despite global reliance on cows for thousands of years, most people's perception of them is as plodding herd animals with little individual personality and very simple social relationships or preferences. Yet, a review of the scientific literature on cow behavior points to more complex cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 178 publications
(175 reference statements)
1
23
0
Order By: Relevance
“…Recently, there has been a growth in interest in the connections between personality, health, welfare, and productivity in farm animals [ 1 , 2 ]. It has been suggested that different personalities may vary in terms of their disease susceptibility [ 3 ], physiological response to stress [ 4 , 5 ] and production traits [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growth in interest in the connections between personality, health, welfare, and productivity in farm animals [ 1 , 2 ]. It has been suggested that different personalities may vary in terms of their disease susceptibility [ 3 ], physiological response to stress [ 4 , 5 ] and production traits [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although dogs demonstrate both behavioral and physiological indictors of social bonding with their owners (Berns, Brooks, & Spivak, 2015;Cook, Prichard, Spivak, & Berns, 2016;Konok, Nagy, & Miklósi, 2015), studies with lambs and cows show no obvious emotional bonds or connections with familiar humans, especially under stress conditions or potential opportunities for bonding (Coulon et al, 2013;Rushen, Munksgaard, Marnet, & DePassillé, 2001). There is evidence, however, to suggest conspecifics bond within herds of cows (Marino & Allen, 2017) and horses (Hartmann, Søndergaard, & Keeling, 2012) and additional support of interspecies social bonding in groups of mixed herbivores (Proops, Burden, & Osthaus, 2012). These studies suggest that domestic herbivores are capable of social bonding within and between species.…”
Section: The Horse-human Bond and Practicing Interpersonal Relationshipsmentioning
confidence: 99%
“…This contradiction between knowing and being is crystallized around the question I posed to lairage workers and farmers which was whether the cows know what is happening when they are brought to the slaughterhouse. I contend that an acknowledgement of the cow's ability to know that something bad is happening is indicative of a sentience beyond the immediate (see Marino & Allen, ), acknowledging their ability to smell the blood of conspecifics (Terlouw, Boissy, & Blinet, ), initiating fear and a desire to escape.…”
Section: Knowing and Beingmentioning
confidence: 99%